ANALISIS PERBEDAAN QIRAAT PADA AYAT-AYAT BIMBINGAN DAN KONSELING ISLAM - Aulia, Fitri (AL-TAZKIAH, 2014)
Quran is the center of human attention and progress (man and his betterment).Quran with all its uniqueness universal must continue to be studied by all the Muslims.Â Especially if you pay attention to its function as a survival guide and legal basis for theÂ life of Muslims. Belong to the realm of scientific development of Islamic counseling.Â Counseling is a product of Islamic culture and ideals of the UIN LOVE interconnectÂ integration. The purpose of this study is to identify the existence of differences in theÂ number of verses qiraâah Counseling. Method that used is library research, with contentÂ analysis. The result of this research is, find three entries based Islamic guidance andÂ counseling is: An-Nahl: 125, Ali-Imran: 104, and Ali-Imran: 110. The entry ofÂ dissimilarity is An-Nahl: 125. There are in a word â ÙÙÚ¾ÙÙÙ although itâs not principle, andÂ not given big effect for the application servis of guidance and counseling.